A Life-Threatening Complication in a Patient with Ehlers-Danlos Syndrome Musculocontractural Type - Tuğba Daşar; Sandra Donkervoort; Pelin Özlem Şimşek Kiper; Rahşan Göçmen; Gülen Eda Utine; Koray Boduroğlu; Carsten Bonnemann; Göknur Haliloğlu (Galenos Yayinevi, 2022)
Ehlers Danlos syndrome musculocontractural type (mcEDS) is a rare hereditary connective tissue disorder caused by biallelic pathogenic variants in the CHST14 or dermatan sulfate (DS) epimerase genes resulting in defective DS biosynthesis. It is characterized by congenital malformations and contractures, distinctive facial features and multisystemic fragility-related complications. To date, less than 100 patients with mcEDS have been reported. Vascular complications remain the major morbidity and may lead to mortality in the affected individuals. In this clinical report, we report on a currently 12-year-old boy with a novel homozygous CHST14 variant who presented with typical mcEDS symptoms and subsequently developed a life-threatening subcutaneous skull hematoma following a minor trauma, which required intensive care unit admission and surgical drainage along with several blood transfusions. This case expands the clinical and genetic spectrum of CHST14-related mcEDS which is essential for providing accurate prognosis, management and genetic counseling.